THE INFLUENCE OF HUMAN RESOURCE TRAINING ON THE PERFORMANCE OF EMPLOYEES IN THE MAKASSAR CITY EDUCATION OFFICE - Faiq Rifa Syawal; Nurman, Rezky Amalia Hamka, Romasnyah Sahabuddin, Uhud Darmawan Natsir (CV. Adiba Aisha Amira, 2025)
This research is a quantitative research that aims to determine the effect of human resource training on employee performance in the Makassar City Department of Education. The population in this study were employees working in the Makassar City Department of Education with a sample of 32 employees. The data collection technique used was a questionnaire. The analysis technique used was multiple linear regression using the Statistical Product and Service Solution (SPPS). The results of the study showed that there was a positive and significant effect of Human Resource Training on Employee Performance at the Makassar City Department of Education.